2016
DOI: 10.1177/1470320316666749
|View full text |Cite
|
Sign up to set email alerts
|

The association of ACE gene polymorphism with diabetic kidney disease and renoprotective efficacy of valsartan

Abstract: Introduction:To investigate the associations between the insertion/deletion (I/D) polymorphisms in the angiotensin converting enzyme (ACE) gene and susceptibility to diabetic kidney disease (DKD); and the efficacy of valsartan in reducing the urine protein in Type 2 diabetes mellitus (T2DM) patients.Materials and methods:We enrolled 128 T2DM patients in this study, including 54 cases with DKD (DKD+) and 74 controls (DKD–). The ACE polymorphism was assayed by polymerase chain reaction (PCR), and the genotype di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…Thus, COVID-19-associated decrease in ACE2 most likely results in disruption of the ACE/ACE2 balance in the kidney leading to sustained activation of ACE and Ang-II activities and kidney damage. ACE insertion/deletion polymorphism is also associated with diabetic kidney disease, the frequency of DD and ID genotype distribution being higher compared with non-diabetic kidney disease cohorts, leading to functional decline [50,51]. The above observations suggest that presence of the DD genotype of ACE in patients with COVID-19 infection may be associated with severe respiratory distress compared with the other genotypes.…”
Section: Ace Insertion/deletion (Id) Polymorphisms: Prevalencementioning
confidence: 89%
“…Thus, COVID-19-associated decrease in ACE2 most likely results in disruption of the ACE/ACE2 balance in the kidney leading to sustained activation of ACE and Ang-II activities and kidney damage. ACE insertion/deletion polymorphism is also associated with diabetic kidney disease, the frequency of DD and ID genotype distribution being higher compared with non-diabetic kidney disease cohorts, leading to functional decline [50,51]. The above observations suggest that presence of the DD genotype of ACE in patients with COVID-19 infection may be associated with severe respiratory distress compared with the other genotypes.…”
Section: Ace Insertion/deletion (Id) Polymorphisms: Prevalencementioning
confidence: 89%
“…It has certain protective effects on glomeruli by inhibiting angiotensin. Evidences from previous studies suggested that valsartan could remarkably lower the glomerular filtration rate and the production of proteinuria, playing a protective role in renal function in patients with type 2 diabetes [ 33 , 34 ]. α-lipoic acid is an antioxidant that can protect β cells, lower the level of cholesterol, reduce proteinuria and mesangial expansion in diabetic mice, thus inhibiting the development and progression of DN [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also exists in glomerular endothelial cells, mesangial cells, podocytes, and distal nephrons. Due to the crucial role of ACE in the RAAS, a large number of studies have linked its polymorphisms to the development of diabetic microvascular complications, such as DN [63]. ACE I/D is the most susceptible locus for DN.…”
Section: Genes Related To the Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%